UNVEILING THE COMMUNITY'S LENS: ASSESSING NGO-LED EDUCATIONAL INITIATIVES ON GIRLS’ EDUCATION IN CHANDRADIH VILLAGE, PURULIA (International Journal of Food and Nutritional Sciences, 2022)
There is a multitude of evidence in available pool of literature that NGOs play significant role in different aspects of societal development like public health, awareness as well as resolving other social and environmental issues especially in developing countries. In India Government School education system faces different issues regarding quality education, where 100 percent enrolment is a challenge and dropout rate is significantly increasing. As a consequence, the issues of access and equity in education have become more pronounced: socio-economically women and girls are worse off, rural areas more marginalized and minorities are under threat. In this situation, educational initiatives of NGOs helps for mainstreaming or supporting the Government educational mission which further help to achieve the Sustainable Development Goals especially goal 04 (i.e. Quality education). Many NGOs are engaged in educational programme at grassroots level particularly in remote, slum and rural backward areas. The proposed study was conducted in Chandradih, a backward village of Purulia district where CESR has been operating their educational centre from the last 5 years. The main purpose of this study is to find out the perception of parents towards CESR’s educational activities. For achieving this goal, a qualitative research method will be adopted and data will be collected from 30 parents through a focus group discussion.